The Philippines - Quan, Ryan Jeremiah D (Archīum Ateneo, 2019)
Human rights and peace education (HRPE) has never been more relevant for the Philippines. As of this writing, there have been opposing views and experiences on key national issues concerning human rights and peace in the country. There have also been apparent disagreements and malpractice with regards to human rights protection, as well as the proliferation of discourses, paradigms, and policies, that seem to trivialize and abuse human life and the rule of law. Therefore, it is imperative to strengthen HRPE and ensure that it is grounded on truth and what is happening at the grassroots level. Despite these challenges, this study shows that HRPE continues to evolve in the Philippine educational system. This study focuses on the current changes adopted by the Philippines with respect to human rights legal education, particularly the developments made by the Legal Education Board (LEB) from 2013 until late 2018. This is the area in which most of the developments are found. Peace and conflict-related programmes offered by colleges and universities are also explored in the study. Desk research on available curricula and programmes of higher education institutions (HEIs) was performed. If the data gathered through desk research were insufficient, necessary information was gathered through validation interviews. Key informant interviews were also conducted with Atty. Marian Chavez, the incumbent Executive Officer of the LEB; Atty. Tanya Karina Lat, one of the consultants of the LEB; and some students from various law schools around the country. The study also reviewed pertinent documents submitted to the LEB by the law schools, and the 2006 research study entitled, “Baseline Study of Law Schools: Human Rights Offerings and Programs Curriculum Review and Development Towards Alternative Lawyering” by Atty. Ma. Ngina Teresa V. Chan-Gonzaga.1 Qualitative analysis is used in analysing the recent developments in HRPE. To supplement the findings, the study also compares the current findings with those of the mapping report published in 2013.2